Sociolinguistic Factors of Language Learning (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The present study investigates the sociolinguistic variables that affect language acquisition in emphasizing the relevance of social, cultural, and environmental contexts in the learning of a foreign language, wherein sociolinguistics scrutinizes the interface between the language and society, with consequent influences on the social interaction, cultural identity, and social status overtime to affect the learners' motivation and success in language learning. Therefore, some major issues are presented that define and shape learners' languages experience in terms of social interaction such as community interaction, peer group pressures, language prestige, and socioeconomic status.